2020
DOI: 10.1042/bsr20201275
|View full text |Cite
|
Sign up to set email alerts
|

Silencing circSLAMF6 represses cell glycolysis, migration, and invasion by regulating the miR-204-5p/MYH9 axis in gastric cancer under hypoxia

Abstract: Background: Gastric cancer (GC) is a malignant tumor of the digestive tract. Hypoxia plays an important role in the development of cancer, including GC. The present study aimed to investigate the role of circular RNA SLAMF6 (circSLAMF6) in the progression of GC under hypoxia. Methods: The expression of circSLAMF6, microRNA-204-5p (miR-204-5p) and myosin heavy chain 9 (MYH9) was measured by quantitative real-time polymerase chain reaction (qRT-PCR). GC cells were maintained under hypoxia (1% O2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The predicted regulatory network showed that upregulated miR-221 and miR-222 and downregulated miR-204 leads to a subsequent cascade promoting thyroid cancer pathway ( Figure 7 ). A systematic review demonstrated multiple deregulated signaling pathways and mechanisms leading to tumor development ( Table S9 ) [ 28 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…The predicted regulatory network showed that upregulated miR-221 and miR-222 and downregulated miR-204 leads to a subsequent cascade promoting thyroid cancer pathway ( Figure 7 ). A systematic review demonstrated multiple deregulated signaling pathways and mechanisms leading to tumor development ( Table S9 ) [ 28 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hsa_circ_0000144 deficiency suppressed glycolysis, metastasis and tumorigenesis of GC cells under hypoxia through the regulation of miR-204-5p/MYH9 axis. 27 In addition, hsa_circ_0000144 sponged miR-623 to upregulate GPRC5A expression, so as to promote GC progression. 28 In keeping with former discoveries, we also detected the upregulation of hsa_circ_0000144 in GC tissues and cells, especially in OXA-resistant tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unlabelled dNTPs, DNase I, T7 RNA polymerase, Klenow fragment exo-, Klenow reaction buffer, RiboLock™, RNA size standards, and T4 polynucleotide kinase were purchased from ThermoFisher Scientific (Schwerte, Germany). Radioactively labelled ATP ([γ-[ 32 ]P]ATP) was obtained from PerkinElmer® (Groningen, Netherlands), T4 RNA Ligase I (T4 RnL) and the appropriate buffer from New England Biolabs (Frankfurt am Main, Germany). DNA primers were purchased from eurofins Genomics (Ebersberg, Germany), RNA oligonucleotides (21mers) were provided by IBA (Goettingen, Germany).…”
Section: Methodsmentioning
confidence: 99%